Acceleration and maximum sprinting speed sprint performance differences in elite and sub-elite ladies gaelic football: a preliminary analysis - McGuinness, E.; Beattie, K.; Lyons, M.; Lane, A.; Higginbotham, C.; Healy, R. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Gaelic football is a multidirectional field-based team sport. The sport requires a range of appropriately developed physical qualities, with speed being crucial (Malone et al., 2023). Acceleration is vital as it allows players to pursue opponents and compete for possession while maximum sprinting speed enables players to evade opponents and create scoring opportunities. Mooney et al. (2019) reported significantly faster 5 and 20 m sprint times (effect sizes: 0.38 to 0.88) in elite men`s Gaelic football U20 players compared to sub-elite players. Acceleration and maximum sprinting speed differences in elite and sub-elite ladies Gaelic football have yet to be investigated. Therefore, the current study aimed to determine the acceleration and maximum sprinting speed differences between elite and sub-elite ladies Gaelic football. METHODS: Twenty-four elite (23.3 ± 4.2 years, 1.67 ± 0.06 m, 67.9 ± 6.7 kg) and sixty-three sub-elite (25.8 ± 7.9 years, 1.67 ± 0.07 m, 65.1 ± 8.6 kg) ladies Gaelic football players participated in the current study. Participants performed two maximal effort sprint trials over 40 m. Sprint performance was monitored using dual-beam timing gates placed at 5 m intervals. The fastest time over a 5 m interval served as a proxy for maximum sprinting speed, while sprint times at 5 and 20 m were used to gauge acceleration performance. Normality of the data was assessed via a Shapiro-Wilk test using an alpha level of 0.05. Independent t-tests and Mann-Whitney tests were performed to assess differences in sprint times and maximum sprinting speed, respectively. Cohen`s d effect sizes were used to assess the standardised differences between playing standards. RESULTS: Descriptive statistics (mean ± SD) for maximum sprinting speed were 7.09 ± 0.43 m.s-1 for sub-elite and 7.57 ± 0.37 m.s-1 for elite players. The median (IQR) for 5 and 20 m times were 1.18 (0.08 s) and 3.47 (0.25 s) for the sub-elite and 1.13 (0.06 s) and 3.28 (0.16 s) for the elite cohort. Elite players were found to have significantly (p < 0.001, cohen`s d = 0.41, small) faster maximum sprinting speed in comparison to sub-elite players. The Mann-Whitney tests revealed that elite players were significantly (U = 425, p = 0.002, U = 306.5, p < 0.001) faster over 5 m and 20 m than their sub-elite counterparts. CONCLUSION: The preliminary findings suggest that elite Ladies Gaelic football players had a significantly faster 5 and 20 m time and achieved a significantly faster maximum sprinting speed than their sub-elite counterparts in a 40 m sprint performance test. Future work should investigate if positional differences exist within the two cohorts.